Formulation & Evaluation of Oral Disintegrating Tablet of Atomoxetine - Selora Agasti; Sarada Prasanna Swain (International Journal of Pharmacy and Analytical Research, 2026)
The present investigation aimed to formulate and evaluate oral disintegrating tablets (ODTs) of Atomoxetine hydrochloride to improve patient compliance and achieve rapid onset of action in attention-deficit/hyperactivity disorder (ADHD). ODTs were prepared by direct compression using Crospovidone, Sodium Starch Glycolate (SSG), and Croscarmellose Sodium (Ac-Di-Sol) at varying concentrations. Tablets were evaluated for physicochemical properties, including thickness, hardness, weight variation, friability, wetting time, dispersion time, disintegration time, drug content uniformity, and in vitro drug release. Compatibility studies using Differential Scanning Calorimetry (DSC) and Fourier Transform Infrared Spectroscopy (FTIR) confirmed the absence of drug–excipient interactions, indicating formulation stability. All formulations complied with pharmacopoeial requirements for ODTs. Among nine formulations, AXODT6 containing optimized SSG showed superior performance with the shortest wetting and disintegration times, highest drug content uniformity, and nearly complete drug release (≈99.33%). Dissolution studies demonstrated rapid drug release from all formulations, with SSG-based tablets outperforming Crospovidone and Ac-Di-Sol. Release kinetics predominantly followed First-order and Higuchi models, with Korsmeyer–Peppas analysis indicating non-Fickian diffusion. AXODT6 exhibited an excellent Zero-order release profile, suggesting controlled and predictable release. The study concludes that Atomoxetine ODTs can be successfully developed by direct compression, and AXODT6 represents a promising patient-friendly dosage form with improved compliance and therapeutic efficacy.